Targeted discovery and identification of novel nucleoside biomarkers in Apostichopus japonicus viscera using metabonomics. (4th March 2019) - Zhang, Xuan-Ming; Han, Li-Wen; Zhang, Shan-Shan; Li, Xiao-Bin; He, Qiu-Xia; Han, Jian; Wang, Xi-Min; Liu, Ke-Chun
Abstract: In this study, we investigated the metabonomic profiles of Apostichopus japonicus using an LC-MS-based method in conjunction with multivariate data analysis. Based on the PLS-DA model, 85 differential metabolites (VIP value >1.0) were obtained from viscera and body wall samples. The MS/MS and NMR experiments were used for the qualitative identification of the characteristic peaks. Sphingoid-based nucleoside analogues were the main components in Chinese A. japonicus viscera. Our findings demonstrate that A. japonicus viscera contain a large number of compounds that may have applications as nutraceuticals or pharmaceuticals.